Analisis Indeks Kualitas Tanah Pada Beberapa Satuan Penggunaan Lahan Di Sub DAS Manten - Pradana Fajar Gumilar; Maroeto Maroeto; Bakti Wisnu Widjajani (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
The Manten Sub-watershed faces land degradation problems due to improper land management. This study aims to identify the soil physical quality index across various land use types in the Manten Sub-watershed and to evaluate potential improvement alternatives. A descriptive quantitative method was applied by analyzing the Soil Physical Quality Index (SPQI) through the measurement of soil physical parameters such as bulk density, particle density, texture, structure, porosity, permeability, and soil organic carbon. Three land use types were evaluated in this research, including dryland or upland, rice field, and garden. Five sampling points were determined to score SPQI for each land use type. The results show that dryland farming and paddy fields can be classified as moderate to slightly good, with SPQI score values ranging from 0.57–0.73 and 0.63–0.70, respectively. Meanwhile, garden land use is classified as fairly good with SPQI score values of 0.70–0.73. Suggested improvement alternatives include the addition of organic matter and the implementation of soil conservation practices, such as proper tillage, cover cropping, and crop rotation.